Raising standards in clinical research - The impact of the ECRIN data centre certification programme, 2011-2016 - Ohmann, C; Canham, S; Demotes, J; Chêne, G; Lauritsen, J; Martins, H; Mendes, R V; Nicolis, E B; Svobodnik, A; Torres, F (Contemporary clinical trials communications, 2017)
The nature and the purpose of the ECRIN Data Centre Certification Programme are summarised, and a very brief description is given of the underlying standards (129 in total, divided into 19 separate lists). The certification activity performed so far is described. In a pilot phase 2 centres were certified in 2012. Calls in 2014 and 2015 resulted in a further 8 certified centres, with 2 certifications still in progress, and the 2016 call has generated several additional applications. The impact and benefits of the programme are listed, divided into a) the effects of the introduction of the standards, b) the effects of the certification programme in general, and c) the effects of the certification programme on individual units. The discussion emphasises the generally positive impact of the programme so far but stresses the need to better clarify the perspective and role of the programme.